Research status and new design concept of compressed air energy storage technology in abandoned mine - Hanpeng WANG; Yunhao WU; Bing ZHANG; Jianguo FAN; Mengtian LI; Jiancai SUI; Wei WANG; Dekang SUN (Meitan kexue jishu)
Compressed air energy storage(CAES) can be widely used in power grid peak load shifting and large-scale new energy consumption. It has the advantages of large installed capacity, long service life, and clean environmental protection, and is regarded as one of the most promising large-scale energy storage technologies. Currently, CAES gas storage are mainly built based on layered salt caverns or salt dome. However, due to strict site selection conditions and other reasons, the development of the CAES industry is greatly limited. Recently，with the closure of a large number of mines, many underground space resources have been wasted. Therefore, using abandoned mines to build CAES power stations has enormous ecological, economic benefits and vast development prospects. This paper systematically sorts out the construction status, advantages and disadvantages of various CAES gas storages, summarizes the construction and site selection requirements of CAES gas storages in abandoned mines, and analyzes the safety risks and limiting bottlenecks faced by CAES gas storages in abandoned mines. In order to avoid the safety risks in the construction and operation of CAES gas storage, we put forward a new gas storage construction scheme “pipeline layout type abandoned mine gas storage (using large diameter seamless steel pipeline as gas storage space, filling loose filling body in the gap to bear pressure)”. Compared with traditional gas storage construction scheme, this scheme has the following advantages: Greatly reduces the site selection requirements of CAES gas storage for geological structure, surrounding rock permeability, surrounding rock stability and other conditions in the mining area, and increases the site selection range; Existing pipeline construction processes and technical equipment can be utilized to reduce the difficulty of constructing gas storage; Improve the sealing performance of CAES power station gas storage to prevent gas leakage; Improve the stress environment of surrounding rock and the stability of gas storage; Avoid the impact of corrosion on the gas storage increases its durability. Finally, takes Ezhuang abandoned coal mine as an example, this paper gives the reconstruction and construction scheme of pipeline layout gas storage. After the reconstruction and construction of gas storage is completed, the total volume can reach 4.5×105 m3, and the power generation can reach 400 MW, which can produce good economic benefits. The pipeline layout type abandoned mine gas storage provides a new idea for the development of CAES technology in abandoned mines, it has the potential for large-scale promotion and application.